Network meta-analysis of deaths from various underlying diseases after COVID-19 infection - Yang, Jinqiang; Li, Ming; Zhang, Renmin (Frontiers in Public Health, 2022)
Network meta-analysis of deaths from various underlying diseases after COVID-19 infection. This study included more than 10 research centers with the same level of care .1676 subjects were included in our study.including 1122 males and 554 females, patients diagnosed with COVID-19 and combined with underlying diseases; provided data on the number of deaths from related diseases. hypertension, diabetes;heart, disease, Dcerebrovascular disease, malignant tumor; chronic kidney disease; chronic liver disease; respiratory disease. the comparison RR between hypertension and different diseases shows that it is (RR=2.35, 95% CI: 1.47, 3.98) compared with diabetes, compared with coronary heart disease (RR=2.57, 95% CI: 1.5, 4.4), compared with cerebrovascular disease (RR=3.68, 95% CI: 1.87, 7.29), compared with malignant tumor (RR=6.35, 95% CI: 3.45, 11.97), and compared with chronic kidney disease (RR=5.53 95% CI: 3.04, 10.34), Compared with chronic liver disease (RR=15.51, 95% CI: 5.26, 50.98), compared with respiratory diseases (RR=4.35, 95% CI: 2.37, 7.65), RR values are greater than 1, which is statistically significant. The surface under the cumulative ranking curve (SUCRA) showed that the ranking of disease mortality from high to low was hypertension> diabetes> heart disease> cerebrovascular disease> respiratory disease> chronic kidney disease> malignant tumor> chronic liver disease. The study that hypertension, diabetes, and heart disease are the top three risk factors for patients infected with COVID-19, and management of these patients should be strengthened to improve the prognosis of patients. Ethical approval and patient consent are not required as this study is a meta-analysis based on published studies. The results of this network meta-analysis will be submitted to a peer-reviewed journal for publication.s